Binary polymer systems for biomedical applications. (17th February 2023) - Afshar, Ayda; Gultekinoglu, Merve; Edirisinghe, Mohan
ABSTRACT: Binary polymer systems provide significant advantages in the preparation of materials used in biomedical applications. To highlight the importance and need of binary polymer systems in biomedical applications; utilisations of nano-carrier and fibre are discussed in detail in terms of their use as biomaterial, and their potential for further development with focus on dual and sequential drug delivery applications. On the other hand, in fibre technology, creation of binary polymer systems have been investigated using spinning processes such as electrospinning and even more recently innovated pressurised gyration. How these methods can be used to promote the mass production of binary polymer systems with various morphologies and characteristics are elucidated. The effects of different polymer materials, including solvents, mechanical properties, and the rate of degradation of polymers, are discussed. Current polymer blending systems and manufacturing processes are analysed, and technologies for biomaterials are carefully considered with up to date details.